Implementation of 5S for the Small Business Workshop and Machine Shop: Community Service in RTG Custom Project Workshop - Saptaji, Kushendarsyah; Hadisujoto, Ignatius Budi; Wibowo, Djati; Ifat; Putra, Indra Pertama; Nurprihatin, Filscha; Oktaviandri, Muchamad; Abdillah, Sultansyah Reza; Handika, Raditya Edra Raja; Lanaggalih, Jarvis Eros; Wong, Miguel Silvano Hermawan (Journal of Community Services: Sustainability and Empowerment, 2024)
The implementation of the Japanese 5S methodology in a small motorcycle workshop in Bogor, Indonesia, has demonstrated significant improvements in workplace organization, operational efficiency, and safety. As Indonesia continues to lead motorcycle sales in the ASEAN region, the need for well-structured and efficient workshops becomes increasingly critical. However, many small businesses still struggle with inadequate organization and risk management. By applying the 5S principles—Sort (Sisih), Set in Order (Susun), Shine (Sapu), Standardize (Standar), and Sustain (Sinambung)—the workshop experienced reduced disorder, improved workflow, enhanced cleanliness, and well-defined procedures. These changes positively impacted productivity, workplace safety, and customer perception. Initial resistance to change was mitigated through comprehensive training and staff engagement, ensuring long-term adoption. This initiative aligns with Sampoerna University’s commitment to community development and serves as a scalable model for small businesses. With adequate government and NGO support, the 5S framework can enhance efficiency, competitiveness, and working conditions in Indonesia’s expanding motorcycle industry.